2013
DOI: 10.1057/mel.2013.1
|View full text |Cite
|
Sign up to set email alerts
|

An input-output-based methodology to estimate the economic role of a port: The case of the port system of the Friuli Venezia Giulia Region, Italy

Abstract: A b s t ra c t The article illustrates the results of a research project aimed at identifying the main economic and industrial characteristics of the port system of the Friuli Venezia Giulia (FVG) Region, Italy, and the role it plays within the economy. Combining a top-down and bottom-up approach, based on interviews and detailed data at firm level, a bi-regional input-output (I-O) table is built with a special disaggregation of the 12 port-related sectors of the FVG region. The I-O table provides the basis fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 39 publications
(36 reference statements)
0
29
0
Order By: Relevance
“…Recently, a major number of studies have been devoted to investigating the effect of seaport investment on national economic growth. The findings of these studies [1][2][3][7][8][9][10][11][12][13] showed that there is a positive relationship between seaport investment and economic growth. Most previous researchers used a production function approach to estimate the effects of seaport investment infrastructure on economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a major number of studies have been devoted to investigating the effect of seaport investment on national economic growth. The findings of these studies [1][2][3][7][8][9][10][11][12][13] showed that there is a positive relationship between seaport investment and economic growth. Most previous researchers used a production function approach to estimate the effects of seaport investment infrastructure on economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Seaport is seen as a determinant of the economic growth, it contributes to the development of economic sectors and to the generation of economic benefits [1][2][3]. Political evaluation of economic impacts of a seaport is usually effectuated by the government to motivate the request for public funds for developing the existing infrastructure or to constructing a new seaport or to justify its social costs.…”
Section: Introductionmentioning
confidence: 99%
“…Ports have been built and developed to support economic and transportation activities since the industrialization era (Jung, 2011). Ports are known as the economic catalysts for the region they serve; the agglomeration of services and manufacturing takes place in ports and generates socio-economic benefits (Warf and Cox, 1989;Pettit and Beresford, 2009;Zhang et al, 2009;Danielis and Gregori, 2013). In fact, in most Asian cities, the port has been the economic backbone, and newly constructed ports integrated with ancillary infrastructures have played a major role in boosting economic growth (Akhavan, 2017).…”
Section: Analysis Of the Possible Impact Of Investment On The Developmentioning
confidence: 99%
“…Firstly, the Input Output Model provides a detailed overview of the underlying relations between all parties involved in port activities, inside and outside the port area. However, the reliability of the data used need to be carefully examined and in many cases data about risk and economic losses may not be available (Coppens et al, 2007;Danielis and Gregori, 2013;Zhang and Cao, 2015). Secondly, the Gravity Model predicts trade flows and therefore economic developments between ports/countries.…”
Section: Literature Reviewmentioning
confidence: 99%